PERAN GURU PAI DALAM MENUMBUHKAN RASA CINTA KEPADA ALLAH DAN RASULULLAH PADA SISWA KLS XI AGAMA 2 DI MADRASAH ALIYAH BABUSSALAM KALIBENING MOJOAGUNG - Maulana Rizki (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research discusses the role of Islamic Religious Education (PAI) teachers in fostering love for Allah and the Messenger of Allah among students in class XI Religion 2 Madrasah Aliyah Babussalam Kalibening Mojoagung. Love for Allah and the Messenger of Allah is considered an important foundation in forming students' faith and devotion. This research focuses on teachers' efforts to provide education that instills love for Allah and the Messenger of Allah through learning, religious habits, and daily activities such as prayers and group prayers. Apart from that, this research also aims to understand the impact of these activities in strengthening students' Islamic personality and spirituality.